Phorbol myristate acetate and catechol as skin cocarcinogens in SENCAR mice. - Van Duuren, B L (1986)
The enhancement of the carcinogenicity of benzo(a)pyrene (B[a]P) and beta-propiolactone (BPL) by the mouse skin cocarcinogens phorbol myristate acetate (PMA) and catechol were examined in female SENCAR mice, 30 per group. The carcinogen and cocarcinogen were applied simultaneously, three times weekly for 490-560 days. B(a)P and BPL were used at constant doses of 5 and 50 micrograms, respectively, in all experiments. PMA was used at three doses, 2.5, 1.0, and 0.5 micrograms per application, and catechol was used at one dose, 2 mg per application. Control groups included animals that received carcinogen only, cocarcinogen only, acetone only, and no treatment. The carcinogenicity of B(a)P and BPL were enhanced by the cocarcinogens, particularly in terms of tumor multiplicity. For both carcinogens, the most marked cocarcinogenic effects were observed at the lowest dose of PMA used (0.5 microgram per application). This observation applied for days to first tumor, animals with tumors, tumor multiplicity, and incidence of malignant skin tumors. Catechol applied alone did not induce any tumors; with PMA alone there were significant incidences of benign and malignant tumors, e.g., at a dose of only 0.5 microgram per application, 15 of 30 animals had 28 tumors, 5 of which were squamous carcinomas. In two-stage carcinogenesis experiments with 7,12-dimethylbenz(a)anthracene (DMBA) as initiator and PMA as promoter, SENCAR mice showed a greater susceptibility to tumor induction when compared to ICR/Ha mice used in earlier work. This susceptibility was most notable in terms of rate of tumor appearance and tumor multiplicity.